Pilot plant demonstration of energy reduction for RO seawater desalination through a recovery increase - Kim, Seung-Hyun; Lee, Sang-Hyup; Yoon, Jong-Sup; Moon, Seong-Yong; Yoon, Cho-Hee (ELSEVIER, 2007)
Energy reduction through a recovery increase was demonstrated for RO seawater desalination using a pilot plant (5 m(3)/h). Energy reduction was possible through a recovery increase. Based on the relationship developed in this study, a recovery increase from 30% to 5 0% reduced energy consumption by half from 10 kWh/m(3) to 5 kWh/m(3). Achieving the target recovery of 50% depended upon such parameters as temperature, salinity, and operating pressure. The target recovery was possible when seawater temperature was higher than 24 degrees C under the study conditions. When the temperature was low and salinity was high, the target recovery was never achieved. Low seawater temperature together with high salinity required excessive operating pressure (73 bar) for the pilot plant to achieve the target recovery, which led to damage of the RO membranes. Subsequently, the target recovery could not be attained and TDS leakage occurred. Temperature was found important for recovery. The linear relationship between recovery and seawater temperature predicted that recovery could increase by almost twice the temperature, which is more than what is expected from the viscosity effect. Based on the relationship developed, the maximum salinity that this pilot plant could achieve as the target recovery was 33 parts per thousand. As expected, the pilot plant was effective in turbidity removal as well as in red-tide removal.